Study on the Motion Characteristic of Carbon-free Car - Wang Chensheng; Su Fang; Fan Long; Zhang Shaowu (Jixie chuandong)
To study the motion characteristics of S-typed trajectory carbon-free car,and thus to optimize the design and adjustment.Through using the steering link mechanism to achieve carbon-free car S-type trajectory motion characteristic of the steering mechanism,the mathematical model of the relationship between the crank angle and the angle of the front wheels is built and its steering mechanism characteristics simulation is carried out by using MATLAB,the relation diagram of crank angle and the front corner of the is obtained.The mathematical model of the car trajectory is established,the parameters influence on the motion trajectory and their influence law are obtained,the relevant amount of the trajectory amplitude value is found and trajectory motion simulation of the car is carried out by using MATLAB.Eventually,the optimal cosine trajectory with the pile of 0.9 m,the amplitude of 0.095 m is got,the crank length is 21 mm at this time,a theoretical guidance for S-type carbon-free car design and adjustment is provided.